SOCIAL AND ETHNIC IDENTITIES MANIFESTATIONS DURING UKRAINIAN EMIGRANT’S ADAPTATION - Kovalenko A. B.; Bezverkha K. S. (International Journal of Innovative Technologies in Social Science, 2020)
In the article is presented a result of researching the manifestations of social and ethnic identities in the process of adaptation of Ukrainian emigrants who live abroad (28 countries in general). Emigrants have a high level of social identity, and also high levels membership satisfaction, thanks to being a member of their reference group; self-understanding and self-development, grade of belonging and the favor of informal relationships. Middle levels have the scales of in-group grade and cohesion. The low index has been revealed according to the intergroup relationships scale. Social identity levels of emigrants with different duration of living abroad are revealed only according to the intergroup competition. The results show the long emigrant adaptation to the new social environment until they reach the stage of activity, when, on the one hand, they feel like they are in their element, but on the other hand - they cannot forget that it is a different environment and the adaptation process has not been finished yet.